The Charter of Rights and Freedoms - Sharpe, Robert J. (Essentials of Canadian law, 2021)
"Written by two of Canada’s leading constitutional scholars, the seventh edition of The Charter of Rights and Freedoms provides a uniquely accessible yet thorough and objective account of the Canadian Charter. This new edition includes, for the first time, a chapter examining Aboriginal and Treaty rights. The authors examine the manner in which Canadian courts have come to terms with the constitutional protection of rights, focusing on the decisions of the Supreme Court of Canada. The purpose is to explain Charter and Aboriginal rights, their interpretation by the courts, and their practical application. This edition also highlights a number of important cases in recent Canadian law. For example, Conseil scolaire francophone de la Colombie-Britannique refused to accept that controlling the cost of minority-language education, which is a Charter right, would justify limiting that right under section 1. The decision also refused to extend qualified immunities from Charter damage awa rds to government policy decisions. The Frank decision, which struck down the disenfranchisement of Canadian citizens living abroad, and an important new remedies case, Ontario (Attorney General) v G, which will affect suspended declarations of invalidity and applicable exemptions, are both given a detailed and comprehensive analysis. The authors also discuss recent developments in the section 2(b) right to freedom of religion, including both the Ktunaxa Nation decision rejecting an Indigenous group’s claim that a development project would infringe on their right to freedom of religion, and the Trinity Western decisions dealing with a religiously motivated covenant that discriminated against prospective LGBTQ2S+ law students; developments in freedom of expression, including election spending and journalists being required to reveal their sources; the important role played by the Charter in the criminal process, including the Boudreault decision, which extends the protection against c ruel and unusual punishment; and developments in the area of equality rights, including decisions on pay equity and the Fraser case, which deals with pension benefits for women."-- Provided by publisher.